Madhyakālīna Hindī kavayitriyām - Sinhā, Sāvitrī, 1923- (Hindī-Anusandhāna-Parishad granthamālā (University of Delhi. Hindī Vibhāga. Hindī-Anusandhāna-Parishad), 1953)
On the women Hindi poets and their contribution to Hindi poetry.